2018
DOI: 10.1007/s40265-018-1007-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tapentadol Prolonged Release: A Review in Pain Management

Abstract: Tapentadol prolonged release (tapentadol PR) [Palexia® SR in EU] is a long-acting tablet formulation of the strong central analgesic tapentadol, which acts as both a μ-opioid receptor (MOR) agonist and a noradrenaline reuptake inhibitor. Tapentadol PR is approved for chronic pain in various countries, with its EU indication (severe chronic pain manageable only with opioid analgesics) being the focus here. Well-designed trials and clinical practice data support tapentadol PR use in this setting. Short term, tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Tapentadol PR use for up to 2 years has been reported to be generally well tolerated in the clinical trials, pooled analyses and clinical practice studies. 9 In our study, we found that the prevalence of tapentadol PR discontinuation owing to adverse reactions is 16.5%, which was similar to those of other studies about the tolerability of tapentadol in pain therapeutics (13-22%). 3,4 Moreover, we show that the most frequent adverse effects associated with the use of tapentadol PR reported in our unit -nausea, vomiting, constipation, dizziness -are similar to the ones described in previous studies, being these less frequent than those of other opioids.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Tapentadol PR use for up to 2 years has been reported to be generally well tolerated in the clinical trials, pooled analyses and clinical practice studies. 9 In our study, we found that the prevalence of tapentadol PR discontinuation owing to adverse reactions is 16.5%, which was similar to those of other studies about the tolerability of tapentadol in pain therapeutics (13-22%). 3,4 Moreover, we show that the most frequent adverse effects associated with the use of tapentadol PR reported in our unit -nausea, vomiting, constipation, dizziness -are similar to the ones described in previous studies, being these less frequent than those of other opioids.…”
Section: Discussionsupporting
confidence: 89%
“…For these reasons, achieving and maintaining the balance between analgesia and safety difficult. 9 Tapentadol hydrochloride is a centrally acting analgesic indicated for the treatment of chronic severe pain that acts in two ways: through the agonism of µ-opioid receptors, attenuating the upward transmission in the pain pathway; and by inhibiting the reuptake of norepinephrine, leaving more free norepinephrine in the downward pain pathway which allows modulation of the painful stimulus. [3][4][5] The µ-opioid receptor binding affinity of the drug was considerably lower that of morphine in vitro, although its analgesic potency in animal models was only two-or threetimes lower than that of morphine, highlighting the contribution of noradrenaline reuptake inhibitor activity to its analgesic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Clinical and post-marketing studies have found that tapentadol has less opioid-related adverse effects compared to the strong opioids, 71 but the prevalence compared to tramadol still is significantly more. 73 Tapentadol has shown favourable efficacy to the strong opioids, 71,74,75 but this mostly relates to chronic or recurrent pain (cancer and non-cancer), and may be overstated when subjected to systematic reviews. 76,77 Tapentadol also has selected advantages over the strong opioids, including lower risk of dependence and abuse potential, less opioid-related adverse effects, and low risk of pharmacokinetic drug interactions.…”
Section: Place In Therapymentioning
confidence: 99%
“…Tapentadol acts both as a μ-opioid receptor (MOR) agonist and as a noradrenaline (NA) reuptake inhibitor (NRI), thereby generating synergistic analgesic action 57. The elevated NA at spinal synapses leads to inhibition of pain signaling through activation of the inhibitory post-synaptic α-2 adrenoceptor on spinal nociceptive neurones, an action that mimics activity in certain descending inhibitory pathways from brain to spinal cord.…”
Section: Introductionmentioning
confidence: 99%